Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Bài 2:
a) \(x^2-y^2+3x-3y=\left(x^2-y^2\right)+\left(3x-3y\right)\)
\(=\left(x-y\right)\left(x+y\right)+3\left(x-y\right)=\left(x-y\right)\left(x+y+3\right)\)
b) \(5x-5y+x^2-2xy+y^2=\left(5x-5y\right)+\left(x^2-2xy+y^2\right)\)
\(=5\left(x-y\right)+\left(x-y\right)^2=\left(x-y\right)\left(x-y+5\right)\)
c) \(x^2-5x+4=x^2-x-4x+4=\left(x^2-x\right)-\left(4x-4\right)\)
\(=x\left(x-1\right)-4\left(x-1\right)=\left(x-1\right)\left(x-4\right)\)
1.X2-2X-4y2-4y
=x2-2x+1-(4y2+4y+1)
=(x+1)2-(2y+1)2
=>(x+1-2y-1)(x+1+2y+1)
=(x-2y)(x+2y+2)
2.x4+2x3-4x-4
=(x2)2-22+2x3-4x
=(x2-2)(x2+2)+2x(x2-2)
=(x2-2)(x2+2+2x)
\(\:x\left(x^2+x+1\right)-x^2\left(x+1\right)-x+5\)
\(=x^3+x^2+x-x^3-x^2-x+5=5\)
Vậy biểu thức ko phụ thuộc vào biến x
\(\left(x^3+x^2y+xy^2+y^3\right)\left(x-y\right)+2x^4\)
\(=x^4-x^3y+x^3y-x^2y^2+x^2y^2-xy^3+y^3x-y^4+2x^4\)
\(=3x^4-y^4\)